PENERAPAN MODEL PEMBELAJARAN AIR DAN RME PADA PEMBELAJARAN MATEMATIKA - Ririn Arinta Sari (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2015)
In the 2013 curriculum requires students to actively observing, ask, reasoning, trying, exploring, and concluding the material provided by the teacher. Many models of learning that can be applied on the 2013 curriculum at the school to improve students’ achievement. In this study, researchers used two different models of learning can improve mathematics learning achievement, namely AIR learning model (Auditory Intellectually Repetition) and RME learning model (Realistic Mathematics Education).Formulation of the problem in this study is whether there are differences in mathematics learning results set of material relations between students taught using AIR learning model (Intellectual Auditory Repetition) and RME leaning model (Realistic Mathematics Education) in seventh grade at SMP Negeri 3 Waru?. While the purpose of this study was to determine whether there are differences in mathematics learning results set of material relations between students taught using AIR learning model (Intellectual Auditory Repetition) and RME learning model (Realistic Mathematics Education) in class VII SMP Negeri 3 Waru.This is an experimental research. In this study takes two classes as a sample. To determine the sample used sampling methods using purposive sampling. The data collection method used the test and documentation method. While the method of data analysis used statistical data analysis using t-test formula. Based on the results of the analysis of the data, obtained tobserve = 3.27 > ttable = 1.99773, so it can be concluded that there are differences in mathematics learning results set of relations material between students taught using AIR learning model (Auditory Intellectually Repetition) and RME learning model (Realistic Mathematic Education) at seventh grade SMP Negeri 3 Waru. Keywords: RME, AIR, The Result of Mathematic